ANALISIS STANDAR MUTU, DISKON DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KEMBALI BUKU PENDAMPING MAESTRO (Studi pada Sekolah Dasar di Kabupaten Wonogiri) - Endah Prastiwi; Djumali Djumali; Rochmi Widayanti (ITB AAS INDONESIA Surakarta, 2019)
Referring to government regulations regarding the regulation of companion books used in schools, this forces the book producers to innovate in order to produce quality and acceptable books on the market. One of the companion book producers in Central Java is CV Hasan Pratama with the brand Maestro. This study has the purpose to investigate the effect of quality standards, discounts and location on Maestro's companion book repurchase decisions. Samples were taken randomly as many as 115 respondents, but only 99 samples could be used. Research uses a type of quantitative research, and using multiple linear regression analysis techniques. Data was collected by giving questionnaires to teachers who taught elementary school level in Wonogiri District. The results of this study prove that quality standards, discounts and locations have a simultaneous effect on product repurchase decisions. But partially the discount variable has a negative effect on product repurchase decisions. Keywords: quality standards, discounts, location, repurchase decision